Penggunaan Video Animasi “Derita Shella” Dalam Upaya Peningkatan Perilaku Remaja Tentang Kehamilan Dini: The Use of the Animated Video "Selita Shella" in an Effort to Improve Adolescent Behavior About Early Pregnancy - Valentin Elvira Melati (Gema Bidan Indonesia, 2025)
Pregnancy in adolescence had a relatively high medical risk, as the reproductive organs were not sufficiently mature to perform their functions. Efforts to prevent early pregnancy included providing health education that would enable teenagers to make appropriate decisions when encountering signs of pregnancy danger. The aim of this study was to analyze the use of the animated video "Derita Shella" in an effort to improve adolescent behavior regarding early pregnancy. This study used a quasi-experimental design with a Randomized Control Group Pretest-posttest Design. Sampling techniques included Purposive Sampling and Simple Random Sampling. The sample size consisted of 60 teenagers in Poncol Village for the control group. Data collection was done using a questionnaire. Data analysis was conducted using the Wilcoxon test, Mann Whitney test, and n-gain test. The results of this study showed a difference in the increase in knowledge and attitude scores among teenagers who were given health promotion using the animated video and those who were given a leaflet, with p-values for knowledge (0.000) and attitude (0.018) (<0.05). Based on the description above, it can be concluded that the animated video "Derita Shella" had an impact on improving knowledge and attitude among teenagers regarding early pregnancy. It is hoped that educational institutions, future researchers, and healthcare services can use the animated video "Derita Shella" as a tool for promoting health awareness regarding early pregnancy. Keywords: animated video; early pregnancy; knowledge; attitude.